Teacher Perceptions of Project Based Learning in the Secondary Classroom - MacMath, Sheryl; Sivia, Awneet; Britton, Vandy (Alberta Journal of Educational Research, 2017)
This study examines teacher perceptions of their experiences with Project Based Learning (PBL) at a secondary school in Western Canada. This PBL initiative included English language arts, mathematics, science, and digital literacy courses and all the grade nines at this large secondary school. This article reports on two teacher focus group interviews that were part of a larger mixed-methods study (Creswell & Plano Clark, 2007). Results provide specific details regarding conditions for the successful implementation of PBL, challenges and support for current research into PBL, and areas of additional needed research. Cette étude se penche sur les perceptions qu’ont les enseignants de leurs expériences avec l’apprentissage axé sur les projets (PBL—project based learning) dans une grande école secondaire dans l’Ouest canadien. Cette initiative d’apprentissage actif par les projets impliquait les cours d’anglais, de mathématiques, de sciences et de littératie numérique, ainsi que les tous les élèves de la 9e année. Cet article porte sur un élément de cette étude à méthodologie mixte (Creswell & Plano Clark, 2007), soit deux groupes de discussion/entrevues avec des enseignants. Les résultats fournissent des détails sur les conditions nécessaires à la mise en œuvre réussie du PBL, les défis qui en découlent, l’appui pour la recherche actuelle et les domaines qui restent à étudier plus en profondeur.